Environmental Policy and Capital Movements: The Role of Government Commitment - Laura Marsiliani; Thomas I. Renström (Fondazione Eni Enrico Mattei (FEEM), 2003)
This paper explores the relationship between environmental protection and international capital movements, when tax policy is endogenous (through voting). A two-period general equilibrium model of a small open economy is specified to compare the effects of two different constitutions (commitment or no commitment in tax policy), as well as income inequality. Under the commitment regime, the equilibrium is characterised by a lower labour tax, higher environmental tax and less capital moving abroad than in the no-commitment equilibrium. Furthermore, given the degree of commitment, more equal societies are characterised by tougher environmental policy and less capital moving abroad.
Keywords: F20; H21; H23; 330; Environmental policy; international capital movements; time consistency; inequality; political economy; human capital; Umweltpolitik; Kapitalmobilität; Steuerpolitik; Einkommensverteilung; Kleine offene Volkswirtschaft; Theorie